Internet of Things-based Temperature and Humidity Control System - Bastian, Fathony Nur; Sunardi, Sunardi (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
The advancement of the industrial revolution 4.0, the use of automation systems and data processing based on the Internet of Things is a new standard that is widely applied to the production and industrial sectors. Air is an important element for daily life, therefore air must have quality so as not to have a negative impact on the body. Therefore, the solution developed in this research is to create an Internet of Things-based room temperature and humidity control system that can be monitored at any time, from anywhere and at any time. The system designed in this research, the ESP8266 microcontroller is used to control and process data from the DHT-11 sensor which is used to detect air temperature and humidity conditions. The results of data processing are then sent to blynk on the smartphone via an internet connection. The relay will turn on the fan when the temperature value is more than 29 °C and will turn off if the temperature is less than 26 °C. From the system testing carried out in the morning until the evening, the temperature error value is 4.46 and the humidity error value is 6.38%. The ability of the system to turn on the fan when the temperature value exceeds a certain limit can also run well.